Religious Protection from Populist Violence: The Catholic Church and the Philippine Drug War - Brook, Steven (Archīum Ateneo, 2021)
Populists often demonize outgroups while undermining institutions that protect citizens against the abuse of state power. Under these conditions, how can vulnerable communities protect themselves? We argue that actors coupling a normative commitment to human rights with the local organizational capacity to intervene can systematically reduce victimization. Focusing on the Philippine Catholic Church in the country's ongoing “drug war,” we identify five potential mechanisms producing protection. Directly, these actors can raise attention, offer sanctuary, or disrupt enforcement, while indirectly they can shrink vulnerable populations and build local solidarity. We evaluate this argument with a mixed-method research design. A new dataset of over 2,000 drug war killings throughout Metro Manila shows that neighborhoods with a Catholic parish experience approximately 30% fewer killings than those without. Original interviews with clergy and laity in these parishes support both direct and indirect mechanisms, with strongest evidence for attention raising and building community solidarity.